Designing IELTS web-based simulation applications (Reading and Listening) at Language Center Unit of State Polytechnic of Pontianak - Nurul Fadillah (Jurnal ELIT, 2021)
Nowadays, there is a demand for the implementation of IELTS test in Pontianak is still quite difficult to find. In addition, for IELTS test training itself can be quite expensive with special training organized by various English learning guidance scattered in Pontianak. However, on the other hand, the use of IELTS test itself is very useful for many people considering the results of IELTS score to be one of the requirements to be accepted on a campus or reputable institution. So, we need a media like website that can be able to know the outline of questions from the IELTS test itself. Language Center Unit (UPT Bahasa) State Polytechnic of Pontianak is one of the institution which is held IELTS preparation for public Method of system development used is Waterfall method. The software used to build this application is Pear Hypertext Preprocessor (PHP) as a programming language, MySQL as the database server, XAMPP as a local server and Sublime Text 3 as a text editor. This application assists the public in estimating the scores achieved for IELTS test questions online and the website also comes with the information about what an IELTS test is and some unique facts about the IELTS test.